The battle for the Emerald Buddha : Thailand - Hunt, Elizabeth Singer (Hunt, Elizabeth Singer. Secret agents Jack & Max Stalwart, 2017)
When the Emerald Buddha is stolen from the Grand Palace, Jack and his older brother, Max, must face one of the smartest villains they have ever encountered.